Samuel Reber papers - Reber, Samuel, 1864-1933.
Correspondence and memoranda concerning the introduction of the electric telegraph into Japan by the U.S. naval expedition led by Matthew Calbraith Perry in 1854 and the 1922 presentation of gifts relating to Perry's expedition to the imperial household of Japan. Chief correspondents are John J. Carty and Edwin Denby.
Typewritten transcripts in part.
Army officer.
Forms part of: Naval Historical Foundation collection.
Keywords: Carty, John J. -- 1861-1932 -- Correspondence; Denby, Edwin, -- 1870-1929 -- Correspondence; Perry, Matthew Calbraith, -- 1794-1858.; Telegraph -- Japan; Japan -- Foreign relations -- United States; United States -- Foreign relations -- Japan; Army officers